2017
DOI: 10.1002/ejlt.201700262
|View full text |Cite
|
Sign up to set email alerts
|

Convenient and Environmentally Friendly Production of Isostearic Acid with Protonic Forms of Ammonium Cationic Zeolites

Abstract: Three ammonium‐cationic zeolites (ferrierite, ZSM5, and zeolite BETA) are individually analyzed to produce branched‐chain fatty acid (i.e., isostearic acid) from unsaturated linear‐chain fatty acid (ulc‐FA) with up to 98% conversion and 80% selectivity. The SiO2/Al2O3 molar ratio of zeolite, amount of water and choice of additive are found to be the key factors for the efficiency of zeolites in this particular reaction. Detailed characterization of zeolites supports the optimization parameters to produce the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 25 publications
0
23
1
1
Order By: Relevance
“…Theskeletal isomerization of unsaturated fatty acids such as 2a was performed in the presence of H + -ferrierite zeolite catalysts to give,a fter hydrogenation, methyl-branched isofatty acids with ar emarkable selectivity of up to about 80 % [61,62] in contrast to the present industrial process. [58] Addition products of unsaturated fatty derivatives and maleic anhydride as well as various follow-up products are of interest because of their versatile properties in numerous applications.…”
Section: Alkyl-branched Fatty Compounds and Cycloadditionsmentioning
confidence: 99%
“…Theskeletal isomerization of unsaturated fatty acids such as 2a was performed in the presence of H + -ferrierite zeolite catalysts to give,a fter hydrogenation, methyl-branched isofatty acids with ar emarkable selectivity of up to about 80 % [61,62] in contrast to the present industrial process. [58] Addition products of unsaturated fatty derivatives and maleic anhydride as well as various follow-up products are of interest because of their versatile properties in numerous applications.…”
Section: Alkyl-branched Fatty Compounds and Cycloadditionsmentioning
confidence: 99%
“…Comparison with the previous literature is however difficult and has to be done with care as often different reaction conditions and/or additives were used. 5,7,33,34 To interpret the obtained results properly and identify the zeolite characteristics responsible for its activity, a basic kinetic study was performed on the obtained results. A (pseudo)firstorder reaction is considered here, as it can be rationalized based on the reaction mechanism (Scheme 1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, additives like water and triphenylphosphine (TPP) were required to obtain these results. 3,6,7 More extensive research with FER by Wiedemann et al and others has shown that the isomerization of fatty acids likely occurs via pore mouth catalysis, in analogy with the hydroisomerization of n-alkanes with zeolites. 8,9 Therefore, when purely microporous zeolites are applied, a large amount of the catalytically active sites are not accessible and thus inactive during the catalytic reaction.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Die Gerüstisomerisierung von ungesättigten Fettsäuren wie 2 a wurde in Anwesenheit von H + -Ferrierit-Zeolith-Katalysatoren durchgeführt und gibt nach Hydrierung methylverzweigte Isofettsäuren mit einer bemerkenswerten Selektivität von bis zu 80 % [61,62] im Gegensatz zum gegenwärtigen industriellen Prozess. [58] Aufgrund ihrer Eigenschaften sind Additionsprodukte von ungesättigten Fettstoffen und Maleinsäureanhydrid wie auch eine Vielzahl ihrer Folgeprodukte für zahlreiche Anwendungen interessant.…”
Section: Alkylverzweigte Fettstoffe Und Cycloadditionenunclassified